2016
DOI: 10.1108/imds-07-2015-0313
|View full text |Cite
|
Sign up to set email alerts
|

Investigating community members’ eWOM effects in Facebook fan page

Abstract: Purpose – The purpose of this paper is to explore the model of enhancing the electronic word-of-mouth (eWOM) effects through the virtual community by discussing the relationship among sense of virtual community, social influence and eWOM effects. Design/methodology/approach – This research adopted structural equation modeling to test the proposed model, and the structural model showed a good fit. This research sample consisted of 492 mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 96 publications
(120 reference statements)
1
27
0
8
Order By: Relevance
“…Sense of virtual community or membership is defined as members' sense of belonging to the community (Hsu et al, 2016). A high sense of membership indicates high trust and strong relationships among community members (Royo-Vela and Casamassima, 2011).…”
Section: Sense Of Virtual Communitymentioning
confidence: 99%
“…Sense of virtual community or membership is defined as members' sense of belonging to the community (Hsu et al, 2016). A high sense of membership indicates high trust and strong relationships among community members (Royo-Vela and Casamassima, 2011).…”
Section: Sense Of Virtual Communitymentioning
confidence: 99%
“…WOM is defined as communication to exchange opinions and product and service information in people's social network [25,26]. In the information systems and communications field, scholars created the term electronic WOM (e-WOM) because people are now using the Internet to communicate with their social network members [27][28][29]. The WOM network includes everyone who connects to the Internet using computers or mobile phones.…”
Section: Word Of Mouth (Wom)mentioning
confidence: 99%
“…In the past 50 years, numerous scholars have argued that word-of-mouth (WOM) was a crucial research issue [ 22 , 23 , 24 ]. Arndt [ 22 ] reported that WOM is a “marketplace information dissemination mechanism in which customer opinions concerning identified enterprises, products/services, and consumer experiences are communicated through informal interpersonal interactions”.…”
Section: Research Model Literature and Hypothesesmentioning
confidence: 99%